2017
DOI: 10.1088/0026-1394/54/1a/07019
|View full text |Cite
|
Sign up to set email alerts
|

Regional comparison of absolute gravimeters SIM.M.G-K1 key comparison

Abstract: Twelve absolute gravimeters were compared during the regional Key Comparison SIM.M.G-K1 of absolute gravimeters. The four gravimeters were from different NMIs and DIs. The comparison was linked to the CCM.G-K2 through EURAMET.M.G-K2 via the DI gravimeter FG5X-216. Overall, the results and uncertainties indicate an excellent agreement among the gravimeters, with a standard deviation of the gravimeters' DoEs better than 1.3 μGal. In the case of the official solution, all the gravimeters are in equivalence well w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 7 publications
1
2
0
Order By: Relevance
“…FG5#238 is also routinely checked against other absolute gravimeters, in the framework of international and regional inter-comparisons. The results provided by FG5#238 were consistent with the Key Comparison Values (Jiang et al 2012;Greco et al 2015;Newell et al 2017;Pálinkáš et al 2017;Falk et al 2020). Absolute gravimeters are compared for the purpose of assuring their reliability and ensure the traceability of measurements to the SI units.…”
Section: Mt Etna's Gravity and Geodetic Monitoring Networksupporting
confidence: 64%
“…FG5#238 is also routinely checked against other absolute gravimeters, in the framework of international and regional inter-comparisons. The results provided by FG5#238 were consistent with the Key Comparison Values (Jiang et al 2012;Greco et al 2015;Newell et al 2017;Pálinkáš et al 2017;Falk et al 2020). Absolute gravimeters are compared for the purpose of assuring their reliability and ensure the traceability of measurements to the SI units.…”
Section: Mt Etna's Gravity and Geodetic Monitoring Networksupporting
confidence: 64%
“…The FG5#238 has been compared with IMGC-02 at the INRiM gravity laboratory in 2011, during several contemporary field surveys on Etna at two stations in 2009 and during several CIPM key comparisons [36][37][38][39]. The results indicated that there was no large discrepancy between the two instruments, since the measured differences were between −4.0 and +8.3 µGal [22], within the standard uncertainty.…”
Section: Results Of the A10#39 And Fg5#238 Inter-comparison Versus Imgc Gravimetermentioning
confidence: 99%
“…The Chi-square test has not been used in published results of AG comparisons. Nevertheless, inconsistent measurements were investigated based on normalized deviations (Newell et al 2017)…”
Section: Consistency Checkmentioning
confidence: 99%